THE DEVELOPMENT MEDIA QUIZ “LASS UNS SPIELEN” - Marita Putri Pertiwi; Tiksno Widyatmoko (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2018)
The purpose of this research and development is to develop “Lass uns spielen” media which supports German learning process in class X language program of senior high school. The development of “Lass uns spielen” media has been adaptsed from Plomp development media and has been modified into 4 steps : (1) preliminary investigation, (2)design, (3) realization or construction, and (4) test, evaluation and revision. In this research, the instrument used to collect data are questionnaires and observation sheets. The quistionnaires ist fulfilled by validator in order to get the data and the result of the experimental observation is analyzed qualitatively descriptively. Based on the results of the questionnaire and the observation, it indicates that the media “Lass uns spielen” is appropriate to be used as media to support German learning in class X language program of senior high school.